AB1345 Evaluation of macrophage activation syndrome in hospitalised febrile patients with kikuchi-fujimoto disease based on the 2016 eular/acr/printo classification criteria. (12th June 2018) - Ahn, S.S.; Kim, H.J.; Kim, H.W.; Jung, S.M.; Lee, S.-W.; Park, M.-C.; Park, Y.-B.; Song, J.J.
Abstract : Background: The incidence and the risk of MAS in Kikuchi-Fujimoto disease (KFD) have been poorly understood, probably because of the rarity of the disease. Objectives: To evaluate the 2016 classification criteria for MAS in hospitalised febrile patients with KFD and compare the clinical features of MAS in KFD with those of systemic lupus erythematosus (SLE) and adult-onset Still's disease (AOSD). Methods: The records of febrile patients with KFD, hospitalised between November 2005 and April 2017, were reviewed. Patients were evaluated for MAS using the 2016 classification criteria. Clinical and laboratory features between patients with KFD with and without MAS, as well as those of patients with MAS in KFD, AOSD, and SLE were compared. Results: Among 78 patients hospitalised with KFD, 24 had MAS during admission. Patients with MAS had longer hospital stays than patients without MAS and only patients with MAS required intensive unit care and experienced in-hospital mortality. Patients with MAS had higher C-reactive protein, aspartate aminotransferase, alanine aminotransferase, lactate dehydrogenase, and ferritin levels and lower lymphocyte count, platelet count, and total protein and albumin levels. MAS patients with KFD, AOSD, and SLE exhibited different clinical characteristics according to the underlying disease; however, MAS patients with KFD required less intensive immunosuppressive treatment than those with AOSD and SLE. Comparison of HScore (A) and the probability of having hemophagocytic syndrome (B) in KFD patients with MAS and without MAS HScore, hemophagocytic syndrome score; KFD, Kikuchi-Fujimoto disease; MAS, macrophage activation syndrome. Conclusions: The 2016 classification criteria were useful in identifying KFD patients with poor clinical outcome. Although treatment for patients with MAS in KFD, AOSD, and SLE differed according to the underlying disease, the 2016 classification criteria for MAS might aid in stratifying high-risk patients and provide guidance for treatment. References: [1] International journal of dermatology. 2016;55(10):1069–75. [2] Ann Rheum Dis. 2016;75(3):481–9. Acknowledgements: None. Disclosure of Interest: None declared